Transfer Payments and Economic Sector Performance: Input-Output Analysis in Bandung Regency - Teti Sofia Yanti; Anneke Iswani Ahmad; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study analyzes the effect of transfer funds on Bandung Regency's economic sectors in 2022, using input-output table analysis to formulate suitable allocation policies for economic development goals. The research was conducted using the Location Quotient (LQ) method. This research produced an inverse Leontif matrix. Leontif's inverse matrix can be used to analyze the interrelationships between economic sectors in Bandung Regency. Revised: The government transfer expenditure in Kabupaten Bandung in 2022 had a direct impact of IDR 459,979,360,622.89 on the Government Administration, Defense, and Mandatory Social Security sector. The indirect impact or multiplier effect on the other 16 economic sectors was IDR 241,790,256,760.42. Analysis through the Leontief inverse matrix shows that the increase of final demand in all sectors by IDR 1 billion would result in an output increase of IDR 1.53 billion in the Government Administration, Defense, and Mandatory Social Security sector. Conversely, if the final demand in that sector increases by IDR 1 billion, the output of all sectors will increase by IDR 1.02 billion. Therefore, the government transfer expenditure in Kabupaten Bandung positively impacted the growth of all economic sectors.